Utility of double-balloon enteroscopy in patients with left ventricular assist devices and obscure overt gastrointestinal bleeding - Edwards, Adam L.; Mönkemüller, Klaus; Pamboukian, Salpy V.; George, James F.; Wilcox, C. M.; Peter, Shajan (Endoscopy, 2014)
Obscure overt gastrointestinal bleeding (OGIB) is a challenge in patients with left ventricular assist devices (LVADs). We evaluated the utility and safety of double-balloon enteroscopy (DBE) in patients with LVADs in an observational consecutive-patient cohort from a single tertiary referral center. Ten patients with LVADs underwent thirteen DBEs for obscure OGIB. The first OGIB event necessitating DBE occurred after a mean of 512 ± 363 days of LVAD support. All patients underwent DBE, eleven anterograde and two retrograde, with a mean insertion depth 176 ± 85 cm. Diagnostic yield was 69 % with the primary bleeding lesion most frequently found in the mid-bowel. The most common lesions were arteriovenous malformations. Therapeutic yield with argon plasma coagulation (APC), epinephrine injection, and/or hemoclip placement was 89 %. There were no procedure-related complications. DBE in patients with LVADs has good diagnostic yield and high therapeutic yield for obscure OGIB and is safe and well tolerated.